Antibiofilm activity of Cyanobacteria spirulina as an irrigation solution against Enterococcus faecalis - Soesilo, Diana; Pangabdian, Fani; Juniar, Eriza (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Sodium hypochlorite (NaOCl) is currently the golden standard for root canal irrigation. NaOCl at a concentration of 5.25% to 6% can eliminate E. faecalis, but this concentration can increase the risk of toxic effects. Cyanobacteria spirulina is known to produce several secondary metabolites that have antimicrobial activity against gram-positive and gram-negative bacteria. The aim of this study was to determine the antibiofilm power of Cyanobacteria spirulina against the biofilms of Enterococcus faecalis at concentrations of 60 mg/ml, 70 mg/ml, 80 mg/ml, and 90 mg/ml. This research was a true experiment with a post-test only group design. The object of the research was divided into 6 groups. Group 1 was a negative control group, group 2 was a positive control group with 5% NaOCl, group 3, 4, 5, 6 were treatment groups given Cyanobacteria spirulina solution at a concentration of 60 mg/ml, 70 mg/ml, 80 mg/ml, and 90 mg/ml, respectively. Optical density (OD) of bacteria was bound by staining and analyzed by ELISA auto reader with a wave length of 595 nm (OD 595 nm). The results of the LSD test showed that the significance between K+ and P1, P2, P3 (p< 0.005), K+ and P4 (p= 0.129), P1 and P2 (p=0.449), P3 and P4 (p=0.178). Significance of p<0.0005 showed a significant difference between the groups. The data were analyzed using the one-way ANOVA test followed by a double comparison test with the Least Significance Different (LSD) Post Hoc test method. Cyanobacteria spirulina solution at a concentration of 90 mg/ml had the greatest inhibitory effect on the biofilm formation of Enterococcus faecalis.